1963
DOI: 10.1128/jb.85.2.399-409.1963
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Microscopy of Purine Compounds in the Yeast Vacuole

Abstract: Ultraviolet microscopy of purine compounds in the yeast vacuole. J. Bacteriol. 85:399-409. 1962.-Yeast cells (Candida utilis and Saccharomyces cerevisiae) suspended in nitrogen-free medium were exposed to various ultravioletabsorbing biological compounds, particularly nucleic acid constituents. Ultraviolet photomicrography was used to locate these substances in the cells. Purines were taken up readily and concentrated in the vacuoles of C. utilis but not of S. cerevisiae. Crystallization occurred, as observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1964
1964
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Accumulation of these compounds depends on the yeast species, the growth conditions and the stage of growth. The vacuoles of the yeast Candida utilis contain crystals of ureic acid (Roush, 1961), adenine, isoguanine (Svihla et al, 1963) and S-adenosyl-Lmethionine (Svihla and Schlenk, 1960;Nakamura, 1973). The data on the size of the vacuolar pools of nucleosides are very scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of these compounds depends on the yeast species, the growth conditions and the stage of growth. The vacuoles of the yeast Candida utilis contain crystals of ureic acid (Roush, 1961), adenine, isoguanine (Svihla et al, 1963) and S-adenosyl-Lmethionine (Svihla and Schlenk, 1960;Nakamura, 1973). The data on the size of the vacuolar pools of nucleosides are very scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Since methionine stimulates the formation of S-adenosylmethionine in S. cerevisiae (7,9), yet does not adversely affect the sai-1 strains, it was suggested that the mutants may employ a mechanism which limits the rate of S-adenosylmethionine synthesis, or in some other manner limits the accumulation of this compound, thereby avoiding self-inhibition. It was also possible that the sai-1 mutants might resist the effects of S-adenosylmethionine synthesized intracellularly by depositing it in the vacuole, as previously described (8,16,17).…”
Section: Resultsmentioning
confidence: 91%
“…Once in the vacuole the compound is known to be excluded from further participation in cellular reactions (16). The mutants 2284-A3 (met-4) and 2284-E4 (met-4-sai-1) were employed to maximize the uptake of extracellular methionine and to avoid dilution of the specific activity of the methionine before its conversion to S-adenosylmethionine.…”
Section: Resultsmentioning
confidence: 99%
“…The convincing demonstrations by Svihla and co-workers (26)(27)(28) that the ultraviolet microscope can be of considerable use in locating and following the fate of ultraviolet-absorbing substances in living cells provided impetus for the present study. The ability to measure ribonucleoprotein in the chromatoid bodies of living cells has enabled us to draw a much more precise picture of the changes in the concentration of RNA in the cells than has hitherto been possible.…”
Section: Introductionmentioning
confidence: 80%